Pengaruh Model Pembelajaran Explicit Instruction Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam Kelas VIII di Sekolah Menengah Pertama Muhammadiyah 25 Paciran - M. Chotibuddin (Jurnal Pendidikan Islam, 2023)
Islamic religious education subjects are looked down upon by some students because most students think that Islamic religious education subjects are boring because some teachers often use the lecture method when teaching. The Explicit Instruction learning model is a learning model designed to support the student learning process, or also known as the direct teaching model. Explicit Instruction can also be in the form of lectures, demonstrations, training or practice and group work so that students will not feel bored during the lesson because they use a variety of learning models. It is hoped that through the Explicit Instruction learning model it can make it easier for students to study Islamic religious education so that they can achieve satisfactory learning outcomes. This study aims to determine the effect of the Explicit Instruction learning model and to determine student learning outcomes in Islamic religious education subjects, and to determine whether there is a significant influence on the Explicit Instruction learning model in improving learning outcomes in Islamic religious education. This study used a quantitative approach with a total of 55 respondents, using sample data, collecting data using pre-test and post-test questions. The collected data were then analyzed by validity test, reliability test, normality test, homogeneity test, correlation test, and significant test. Based on the calculation results, the data values obtained through the SPSS program version 23.0 for windows. In calculating the hypothesis, the researcher used the product moment correlation test and showed that there was a significant influence on the Explicit Instruction learning model in improving student learning outcomes in Islamic religious education subjects, obtained a value of rxy = 0.736, and for a significant test obtained a value of t = 7.926 at the level significant 5% is 2.005. So from the discussion above it shows that there is a positive and significant influence between the Explicit Instruction learning model in improving student learning outcomes in class VIII Islamic religious education subjects at SMP Muhammadiyah 25 Paciran.